Inovasi Pembelajaran Bahasa Arab Berbasis Digital di MI Mambaul Ulum Dagan Lamongan - Lilik Aisatul Husnah; Syukh Batul Maimanah; Ziyana Walida Salsabila (Edu Journal Innovation in Learning and Education, 2023)
In the world of education, of course there is no escape from learning, where learning is the assistance provided by educators so that the process of acquiring knowledge and knowledge, mastering skills and habits and forming attitudes and beliefs in students can occur. To make this happen, there needs to be innovative learning. This means learning that uses new, creative methods and prioritizes critical thinking. The aim of innovative learning is to develop students' ability to think independently, creatively and innovatively so that students can produce new ideas, solve problems and apply knowledge in their lives. This innovative learning is implemented. Madrasah Ibtidaiyah level students in class 2B memorize mufrodat using digital-based facilities, namely using a television connected to the internet, so that students do not feel bored and also use the singing method. Meanwhile, the method used in this research is a descriptive qualitative method in the form of collecting information. As for the reality, the teacher actually applies a digital-based singing method using a television connected to the internet so that students are very enthusiastic about learning and can memorize mufrodat very easily.